2018
DOI: 10.3389/fnbeh.2017.00257
|View full text |Cite
|
Sign up to set email alerts
|

Discounting and Digit Ratio: Low 2D:4D Predicts Patience for a Sample of Females

Abstract: Inter-temporal trade-offs are ubiquitous in human decision making. We study the relationship between preferences over such trade-offs and the ratio of the second digit to that of the forth (2D:4D), a marker for pre-natal exposure to sex hormones. Specifically, we study whether 2D:4D affects discounting. Our sample consists of 419 female participants of a Guatemalan conditional cash transfer program who take part in an experiment. Their choices in the convex time budget (CTB) experimental task allow us to make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…Sixth, a variety of physiological evidence corroborates the idea that the receipt of a cash reward presents the same as a primary reward. CTB results using cash correlate with pupil dilation (Lempert et al 2015(Lempert et al , 2016 and with 2D-4D digit ratios, an indicator of pre-natal testosterone exposure (Aycinena & Rentschler 2017). Löckenho, O'Donoghue & Dunning (2011) found that discounting and present bias are signicantly correlated with psychological measures of anticipated emotional arousal at receiving monetary payments over time.…”
mentioning
confidence: 99%
“…Sixth, a variety of physiological evidence corroborates the idea that the receipt of a cash reward presents the same as a primary reward. CTB results using cash correlate with pupil dilation (Lempert et al 2015(Lempert et al , 2016 and with 2D-4D digit ratios, an indicator of pre-natal testosterone exposure (Aycinena & Rentschler 2017). Löckenho, O'Donoghue & Dunning (2011) found that discounting and present bias are signicantly correlated with psychological measures of anticipated emotional arousal at receiving monetary payments over time.…”
mentioning
confidence: 99%
“…Alonso et al [15] reported that low digit ratio correlates with high social preference. Again, Aycinena et al [16] in his study asserted that women with low digit ratio tend to be more patient; motioned that a low digit ratio positively correlates with static and explosive strength, speed and agility which is a typical masculine trait exemplified in digit ratio. Furthermore, it was also mentioned that a study on sports activities showed that those who got to the highest level of competition in their respective games had low digit ratios [17] which were mostly men.…”
Section: Discussionmentioning
confidence: 97%
“…There are some reports on investigations by other researchers on digit ratios in various indigenous populations. [9][10][11][12][13][14][15][16][17][18][19][20] There is paucity of information on gender difference in digit ratio in Bini tribe.…”
Section: Introductionmentioning
confidence: 99%
“…A large literature links prenatal sex hormones with economic preferences. While several studies report significant relationships between prenatal testosterone exposure and risk preferences [15][16][17], time preferences [18], trust [19] and social preferences [20], other studies find null effects and conflicting evidence (for reviews, see Apicella et al [21], Parslow et al [22] and Neyse et al [23]). The role that hormones play in the development of preferences is, therefore, not well understood.…”
Section: Introductionmentioning
confidence: 99%